-
Notifications
You must be signed in to change notification settings - Fork 3
/
Copy pathTypeProofs.agda
622 lines (539 loc) · 27.5 KB
/
TypeProofs.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
581
582
583
584
585
586
587
588
589
590
591
592
593
594
595
596
597
598
599
600
601
602
603
604
605
606
607
608
609
610
611
612
613
614
615
616
617
618
619
620
621
module TypeProofs where
open import Type
open import Data.Empty
open import Data.Product renaming (map to pmap)
open import Data.Sum renaming (map to smap)
open import Data.Unit
open import Function using (_$_; _∋_)
open import Relation.Binary.PropositionalEquality
import Function as F
-- Misc util
--------------------------------------------------------------------------------
vs-∈-≡ :
∀ {Γ}{A : Set}{B C} {v v' : A ⊎ (B ∈ Γ)}
→ v ≡ v' → smap F.id (vs_ {B = C}) v ≡ smap F.id vs_ v'
vs-∈-≡ = cong (smap F.id vs_)
-- Categorical stuff for _⊆_
--------------------------------------------------------------------------------
∘-refl : ∀ {Γ Δ} (o : Γ ⊆ Δ) → o ∘ refl ≡ o
∘-refl refl = refl
∘-refl (add o) = cong add (∘-refl o)
∘-refl (keep o) = refl
ren-∈-∘ :
∀ {Γ Δ Ξ A} (o : Δ ⊆ Ξ) (o' : Γ ⊆ Δ) (v : A ∈ Γ)
→ ren-∈ o (ren-∈ o' v) ≡ ren-∈ (o ∘ o') v
ren-∈-∘ refl o' v = refl
ren-∈-∘ (add o) o' v = cong vs_ (ren-∈-∘ o o' v)
ren-∈-∘ (keep o) refl v = refl
ren-∈-∘ (keep o) (add o') v = cong vs_ (ren-∈-∘ o o' v)
ren-∈-∘ (keep o) (keep o') vz = refl
ren-∈-∘ (keep o) (keep o') (vs v) = ren-∈-∘ (add o) o' v
mutual
ren-∘ : ∀ {Γ Δ Ξ A}(o : Δ ⊆ Ξ)(o' : Γ ⊆ Δ)(t : Ty Γ A) → ren o (ren o' t) ≡ ren (o ∘ o') t
ren-∘ o o' (A ⇒ B) = cong₂ _⇒_ (ren-∘ o o' A) (ren-∘ o o' B)
ren-∘ o o' (∀' A B) = cong (∀' A) (ren-∘ (keep o) (keep o') B)
ren-∘ o o' (ƛ t) = cong ƛ_ (ren-∘ (keep o) (keep o') t)
ren-∘ o o' (ne (v , sp)) = cong₂ (λ x y → ne (x , y)) (ren-∈-∘ o o' v) (renSp-∘ o o' sp)
renSp-∘ :
∀ {Γ Δ Ξ A B}(o : Δ ⊆ Ξ)(o' : Γ ⊆ Δ)(sp : Sp Γ A B)
→ renSp o (renSp o' sp) ≡ renSp (o ∘ o') sp
renSp-∘ o o' ε = refl
renSp-∘ o o' (t ∷ sp) = cong₂ _∷_ (ren-∘ o o' t) (renSp-∘ o o' sp)
Id-⊆ : ∀ {Γ} → Γ ⊆ Γ → Set
Id-⊆ refl = ⊤
Id-⊆ (add o) = ⊥
Id-⊆ (keep o) = Id-⊆ o
ren-∈-Id : ∀ {Γ A}(o : Γ ⊆ Γ){{p : Id-⊆ o}}(v : A ∈ Γ) → ren-∈ o v ≡ v
ren-∈-Id refl v = refl
ren-∈-Id (add o) {{()}} v
ren-∈-Id (keep o) vz = refl
ren-∈-Id (keep o) (vs v) = cong vs_ (ren-∈-Id o v)
mutual
ren-Id : ∀ {Γ A}(o : Γ ⊆ Γ){{p : Id-⊆ o}}(t : Ty Γ A) → ren o t ≡ t
ren-Id o (A ⇒ B) = cong₂ _⇒_ (ren-Id o A) (ren-Id o B)
ren-Id o (ƛ t) = cong ƛ_ (ren-Id (keep o) t)
ren-Id o (∀' k t) = cong (∀' k) (ren-Id (keep o) t)
ren-Id o (ne (v , sp)) = cong₂ (λ x y → ne (x , y)) (ren-∈-Id o v) (renSp-Id o sp)
renSp-Id : ∀ {Γ A B}(o : Γ ⊆ Γ){{p : Id-⊆ o}}(sp : Sp Γ A B) → renSp o sp ≡ sp
renSp-Id o ε = refl
renSp-Id o (t ∷ sp) = cong₂ _∷_ (ren-Id o t) (renSp-Id o sp)
ren-refl : ∀ {Γ A}(t : Ty Γ A) → ren refl t ≡ t
ren-refl = ren-Id refl
renSp-refl : ∀ {Γ A B}(sp : Sp Γ A B) → renSp refl sp ≡ sp
renSp-refl = renSp-Id refl
-- Substituting a newly added variable does nothing
--------------------------------------------------------------------------------
Fresh : ∀ {Γ Δ A} → Γ ⊆ Δ → A ∈ Δ → Set
Fresh refl v = ⊥
Fresh (add o) vz = ⊤
Fresh (add o) (vs v) = Fresh o v
Fresh (keep o) vz = ⊥
Fresh (keep o) (vs v) = Fresh o v
Fresh-sub-⊆ : ∀ {Γ Δ A v} o → Fresh {Γ}{Δ}{A} o v → Γ ⊆ subᶜ v
Fresh-sub-⊆ {v = vz} refl ()
Fresh-sub-⊆ {v = vz} (add o) p = o
Fresh-sub-⊆ {v = vz} (keep o) ()
Fresh-sub-⊆ {v = vs v} refl ()
Fresh-sub-⊆ {v = vs v} (add o) p = add (Fresh-sub-⊆ o p)
Fresh-sub-⊆ {v = vs v} (keep o) p = keep (Fresh-sub-⊆ o p)
fresh-∈-eq :
∀ {Γ Δ A B}(o : Γ ⊆ Δ)(v : A ∈ Δ)(v' : B ∈ Γ)(f : Fresh o v)
→ ∈-eq v (ren-∈ o v') ≡ inj₂ (ren-∈ (Fresh-sub-⊆ o f) v')
fresh-∈-eq refl v v' ()
fresh-∈-eq (add o) vz v' p = refl
fresh-∈-eq (add o) (vs v) v' p rewrite fresh-∈-eq o v v' p = refl
fresh-∈-eq (keep o) vz v' ()
fresh-∈-eq (keep o) (vs v) vz p = refl
fresh-∈-eq (keep o) (vs v) (vs v') p rewrite fresh-∈-eq o v v' p = refl
mutual
fresh-sub :
∀ {Γ Δ A B} (o : Γ ⊆ Δ) (v : A ∈ Δ)(f : Fresh o v)(t' : Ty (drop v) A)(t : Ty Γ B)
→ sub v t' (ren o t) ≡ ren (Fresh-sub-⊆ o f) t
fresh-sub o v f t' (A ⇒ B) rewrite fresh-sub o v f t' A | fresh-sub o v f t' B = refl
fresh-sub o v f t' (ƛ t) = cong ƛ_ (fresh-sub (keep o) (vs v) f t' t)
fresh-sub o v f t' (∀' k t) = cong (∀' k) (fresh-sub (keep o) (vs v) f t' t)
fresh-sub o v f t' (ne (v' , sp)) with ∈-eq v (ren-∈ o v') | fresh-∈-eq o v v' f
... | inj₁ refl | ()
... | inj₂ _ | refl = cong (λ x → ne (_ , x)) (fresh-sub-Sp o v f t' sp)
fresh-sub-Sp :
∀ {Γ Δ A B C} (o : Γ ⊆ Δ) (v : A ∈ Δ)(f : Fresh o v)(t' : Ty (drop v) A)(sp : Sp Γ B C)
→ subSp v t' (renSp o sp) ≡ renSp (Fresh-sub-⊆ o f) sp
fresh-sub-Sp o v f t' ε = refl
fresh-sub-Sp o v f t' (x ∷ sp) = cong₂ _∷_ (fresh-sub o v f t' x) (fresh-sub-Sp o v f t' sp)
inst-top : ∀ {Γ A B} (t' : Ty Γ A)(t : Ty Γ B) → inst t' (ren top t) ≡ t
inst-top t' t = trans (fresh-sub top vz _ t' t) (ren-refl t)
inst-top-Sp : ∀ {Γ A B C} (t' : Ty Γ A)(sp : Sp Γ B C) → subSp vz t' (renSp top sp) ≡ sp
inst-top-Sp t' sp = trans (fresh-sub-Sp top vz _ t' sp) (renSp-refl sp)
-- Top commutes with any embedding
--------------------------------------------------------------------------------
top-comm :
∀ {Γ Δ A B}(t : Ty Γ A)(o : Γ ⊆ Δ) → ren top (ren o t) ≡ ren (keep o) (ren (top {B}) t)
top-comm {B = B} t o rewrite ren-∘ (top{B}) o t | ren-∘ (keep o) (top {B}) t | ∘-refl o = refl
top-comm-Sp :
∀ {Γ Δ A B C}(sp : Sp Γ A B)(o : Γ ⊆ Δ)
→ renSp top (renSp o sp) ≡ renSp (keep o) (renSp (top {C}) sp)
top-comm-Sp {C = C} sp o rewrite
renSp-∘ (top{C}) o sp | renSp-∘ (keep o) (top {C}) sp | ∘-refl o = refl
-- Renaming commutes with substitution
--------------------------------------------------------------------------------
ren-sub-∈ :
∀ {Γ Δ A B}(o : Γ ⊆ Δ) (v : A ∈ Γ) (v' : B ∈ Γ)
→ ∈-eq (ren-∈ o v) (ren-∈ o v') ≡ smap F.id (ren-∈ (⊆-subᶜ v o)) (∈-eq v v')
ren-sub-∈ refl v v' with ∈-eq v v'
... | inj₁ _ = refl
... | inj₂ _ = refl
ren-sub-∈ (add o) v v' with ren-sub-∈ o v v' | ∈-eq v v' | inspect (∈-eq v) v'
... | rec | inj₁ _ | [ eq ] rewrite rec | eq = refl
... | rec | inj₂ _ | [ eq ] rewrite rec | eq = refl
ren-sub-∈ (keep o) (vs v) (vs v') with ren-sub-∈ o v v' | ∈-eq v v' | inspect (∈-eq v) v'
... | rec | inj₁ x | [ eq ] rewrite rec | eq = refl
... | rec | inj₂ y | [ eq ] rewrite rec | eq = refl
ren-sub-∈ (keep o) vz vz = refl
ren-sub-∈ (keep o) vz (vs v') = refl
ren-sub-∈ (keep o) (vs v) vz = refl
ren-drop-sub' :
∀ {Γ Δ A}(o : Γ ⊆ Δ)(v : A ∈ Γ)
→ (⊆-subᶜ v o ∘ drop-sub-⊆ v) ≡ (drop-sub-⊆ (ren-∈ o v) ∘ ⊆-drop v o)
ren-drop-sub' refl v = sym (∘-refl (drop-sub-⊆ v))
ren-drop-sub' (add o) v = cong add (ren-drop-sub' o v)
ren-drop-sub' (keep o) vz = ∘-refl o
ren-drop-sub' (keep o) (vs v) = cong add (ren-drop-sub' o v)
ren-drop-sub :
∀ {Γ Δ A}(o : Γ ⊆ Δ)(v : A ∈ Γ)(t : Ty (drop v) A)
→ ren (⊆-subᶜ v o) (ren (drop-sub-⊆ v) t) ≡ ren (drop-sub-⊆ (ren-∈ o v)) (ren (⊆-drop v o) t)
ren-drop-sub o v t rewrite
ren-∘ (⊆-subᶜ v o) (drop-sub-⊆ v) t | ren-∘ (drop-sub-⊆ (ren-∈ o v)) (⊆-drop v o) t
= cong (λ x → ren x t) (ren-drop-sub' o v)
mutual
ren-sub :
∀ {Γ Δ A B} (v : A ∈ Γ) (o : Γ ⊆ Δ) t' (t : Ty Γ B)
→ ren (⊆-subᶜ v o) (sub v t' t) ≡ sub (ren-∈ o v) (ren (⊆-drop v o) t') (ren o t)
ren-sub v o t' (A ⇒ B) rewrite ren-sub v o t' A | ren-sub v o t' B = refl
ren-sub v o t' (ƛ t) = cong ƛ_ (ren-sub (vs v) (keep o) t' t)
ren-sub v o t' (∀' k t) = cong (∀' k) (ren-sub (vs v) (keep o) t' t)
ren-sub v o t' (ne (v' , sp))
with ∈-eq (ren-∈ o v) (ren-∈ o v') | ∈-eq v v' | ren-sub-∈ o v v'
... | inj₁ refl | inj₁ _ | refl
rewrite
sym $ ren-sub-Sp v o t' sp
| ren-◇ (⊆-subᶜ v o) (ren (drop-sub-⊆ v) t') (subSp v t' sp)
| ren-drop-sub o v t'
= refl
... | inj₂ _ | inj₂ v'' | refl rewrite ren-sub-Sp v o t' sp = refl
... | inj₁ refl | inj₂ _ | ()
... | inj₂ _ | inj₁ refl | ()
ren-sub-Sp :
∀ {Γ Δ A B C} (v : A ∈ Γ) (o : Γ ⊆ Δ) t' (sp : Sp Γ B C) →
renSp (⊆-subᶜ v o) (subSp v t' sp) ≡ subSp (ren-∈ o v) (ren (⊆-drop v o) t') (renSp o sp)
ren-sub-Sp v o t' ε = refl
ren-sub-Sp v o t' (x ∷ sp) = cong₂ _∷_ (ren-sub v o t' x) (ren-sub-Sp v o t' sp)
ren-◇ :
∀ {Γ Δ A B}(o : Γ ⊆ Δ) (t : Ty Γ A) (sp : Sp Γ A B) →
ren o (t ◇ sp) ≡ ren o t ◇ renSp o sp
ren-◇ o t ε = refl
ren-◇ o (ƛ t) (x ∷ sp) rewrite
ren-◇ o (inst x t) sp | ren-sub vz (keep o) x t = refl
ren-top-sub :
∀ {Γ A B C}(v : A ∈ Γ) (t' : Ty (drop v) A) (t : Ty Γ B)
→ ren (top {C}) (sub v t' t) ≡ sub (vs v) t' (ren (top {C}) t)
ren-top-sub {C = C} v t' t rewrite ren-sub v (top {C}) t' t | ren-refl t' = refl
-- Substitution commutes with substitution
--------------------------------------------------------------------------------
drop-drop-sub :
∀ {Γ A B}(v : A ∈ Γ){v' : B ∈ drop v} → drop v' ⊆ drop (ren-∈ (drop-sub-⊆ v) v')
drop-drop-sub v {v'} = ⊆-drop v' (drop-sub-⊆ v)
drop-drop : ∀ {Γ A B}(v : A ∈ Γ){v' : B ∈ drop v} → drop v' ⊆ drop (ren-∈ (drop-⊆ v) v')
drop-drop v {v'} = ⊆-drop v' (drop-⊆ v)
_-_ : ∀ {Γ A B}(v : A ∈ Γ)(v' : B ∈ drop v) → A ∈ subᶜ (ren-∈ (drop-⊆ v) v')
_-_ vz v' = vz
_-_ (vs v) v' = vs (v - v')
sub-drop- : ∀ {Γ A B}(v : A ∈ Γ){v' : B ∈ drop v} → subᶜ v' ⊆ drop (v - v')
sub-drop- vz = refl
sub-drop- (vs v) = sub-drop- v
exc : ∀ {Γ A B}(v : A ∈ Γ){v' : B ∈ drop v} → subᶜ (v - v') ⊆ subᶜ (ren-∈ (drop-sub-⊆ v) v')
exc vz = refl
exc (vs v) = keep (exc v)
remove- :
∀ {Γ A B}(v : A ∈ Γ)(v' : B ∈ drop v)
→ (exc v ∘ drop-sub-⊆ (v - v') ∘ sub-drop- v) ≡ ⊆-subᶜ v' (drop-sub-⊆ v)
remove- vz v' = refl
remove- (vs v) v' = cong add (remove- v v')
Fresh- :
∀ {Γ A B}(v : A ∈ Γ)(v' : B ∈ drop v)
→ Fresh (drop-sub-⊆ (ren-∈ (drop-⊆ v) v') ∘ ⊆-drop v' (drop-⊆ v)) (v - v')
Fresh- vz v' = tt
Fresh- (vs v) v' = Fresh- v v'
remove-Fresh- :
∀ {Γ A B}(v : A ∈ Γ)(v' : B ∈ drop v)
→ (exc v ∘ Fresh-sub-⊆
(drop-sub-⊆ (ren-∈ (drop-⊆ v) v') ∘ ⊆-drop v' (drop-⊆ v))
(Fresh- v v'))
≡ (drop-sub-⊆ (ren-∈ (drop-sub-⊆ v) v') ∘ ⊆-drop v' (drop-sub-⊆ v))
remove-Fresh- vz v' = refl
remove-Fresh- (vs v) v' = cong add (remove-Fresh- v v')
sub-sub-∈ :
∀ {Γ A B C}(v : A ∈ Γ)(v₁ : B ∈ Γ)(v₂ : C ∈ drop v₁)
→ (∃₂ λ p v''
→ ∈-eq v₁ v ≡ inj₁ p
× ∈-eq (ren-∈ (drop-⊆ v₁) v₂) v ≡ inj₂ v''
× ∈-eq (v₁ - v₂) v'' ≡ inj₁ p)
⊎
(∃₂ λ p v'
→ ∈-eq v₁ v ≡ inj₂ v'
× ∈-eq (ren-∈ (drop-⊆ v₁) v₂) v ≡ inj₁ p
× ∈-eq (ren-∈ (drop-sub-⊆ v₁) v₂) v' ≡ inj₁ p)
⊎
(∃₂ λ v' v'' → ∃₂ λ w' w''
→ ∈-eq v₁ v ≡ inj₂ v'
× ∈-eq (v₁ - v₂) v'' ≡ inj₂ w'
× ∈-eq (ren-∈ (drop-⊆ v₁) v₂) v ≡ inj₂ v''
× ∈-eq (ren-∈ (drop-sub-⊆ v₁) v₂) v' ≡ inj₂ w''
× w'' ≡ ren-∈ (exc v₁) w')
sub-sub-∈ vz vz _ = inj₁ (refl , vz , refl , refl , refl)
sub-sub-∈ vz (vs vz) vz = inj₂ (inj₂ (vz , vz , vz , vz , refl , refl , refl , refl , refl))
sub-sub-∈ vz (vs vz) (vs v₂) = inj₂ (inj₂ (vz , vz , vz , vz , refl , refl , refl , refl , refl))
sub-sub-∈ vz (vs (vs v₁)) v₂ = inj₂ (inj₂ (vz , vz , vz , vz , refl , refl , refl , refl , refl))
sub-sub-∈ (vs vz) vz vz = inj₂ (inj₁ (refl , vz , refl , refl , refl))
sub-sub-∈ (vs (vs v)) vz vz = inj₂ (inj₂ ((vs v) , (vs v) , v , v , refl , refl , refl , refl , refl))
sub-sub-∈ (vs v) vz (vs v₂) with sub-sub-∈ v vz v₂
... | inj₁ (p , v'' , a , b , c)
= inj₂ (inj₂ (v , (vs v'') , v'' , v'' , refl , refl , vs-∈-≡ b , b , refl))
... | inj₂ (inj₁ (p , v' , a , b , c))
= inj₂ (inj₁ (p , v , refl , vs-∈-≡ b , b ))
... | inj₂ (inj₂ (v' , v'' , w' , w'' , a , b , c , d))
= inj₂ (inj₂ (v , (vs v'') , v'' , v'' , refl , refl , vs-∈-≡ c , c , refl))
sub-sub-∈ (vs v) (vs v₁) v₂ with sub-sub-∈ v v₁ v₂
... | inj₁ (p , v'' , a , b , c)
= inj₁ (p , (vs v'') , vs-∈-≡ a , vs-∈-≡ b , vs-∈-≡ c)
... | inj₂ (inj₁ (p , v' , a , b , c))
= inj₂ (inj₁ (p , (vs v') , vs-∈-≡ a , vs-∈-≡ b , vs-∈-≡ c))
... | inj₂ (inj₂ (v' , v'' , w' , w'' , a , b , c , d , e))
= inj₂ (inj₂ ((vs v') , (vs v'') , (vs w') , (vs w'') , vs-∈-≡ a , vs-∈-≡ b , vs-∈-≡ c , vs-∈-≡ d , cong vs_ e))
mutual
sub-sub :
∀ {Γ A B C}
(v₁ : A ∈ Γ)(v₂ : B ∈ drop v₁)
(t₁ : Ty (drop v₁) A)(t₂ : Ty (drop v₂) B)
(t : Ty Γ C)
→ sub (ren-∈ (drop-sub-⊆ v₁) v₂) (ren (drop-drop-sub v₁) t₂) (sub v₁ t₁ t)
≡
ren (exc v₁) (sub (v₁ - v₂) (ren (sub-drop- v₁) (sub v₂ t₂ t₁))
(sub (ren-∈ (drop-⊆ v₁) v₂) (ren (drop-drop v₁) t₂) t))
sub-sub v₁ v₂ t₁ t₂ (A ⇒ B) = cong₂ _⇒_ (sub-sub v₁ v₂ t₁ t₂ A) (sub-sub v₁ v₂ t₁ t₂ B)
sub-sub v₁ v₂ t₁ t₂ (ƛ t) = cong ƛ_ (sub-sub (vs v₁) v₂ t₁ t₂ t )
sub-sub v₁ v₂ t₁ t₂ (∀' k t) = cong (∀' k) (sub-sub (vs v₁) v₂ t₁ t₂ t)
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp))
with sub-sub-∈ v v₁ v₂
-- Substitute t₁
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ _
with ∈-eq v₁ v | ∈-eq (ren-∈ (drop-⊆ v₁) v₂) v
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ (_ , _ , _ , () , _) | inj₁ _ | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ (_ , _ , _ , () , _) | inj₂ _ | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ (_ , _ , () , _ , _) | inj₂ _ | inj₂ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ (.refl , v'' , refl , refl , _) | inj₁ refl | inj₂ _
with ∈-eq (v₁ - v₂) v''
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ (.refl , _ , refl , refl , ()) | inj₁ refl | inj₂ _ | inj₂ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₁ (.refl , v'' , refl , refl , refl) | inj₁ refl | inj₂ _ | inj₁ refl
rewrite
ren-∘ (drop-sub-⊆ (v₁ - v₂)) (sub-drop- v₁) (sub v₂ t₂ t₁)
| ren-◇
(exc v₁)
(ren (drop-sub-⊆ (v₁ - v₂) ∘ sub-drop- v₁) (sub v₂ t₂ t₁))
(subSp (v₁ - v₂)
(ren (sub-drop- v₁) (sub v₂ t₂ t₁))
(subSp (ren-∈ (drop-⊆ v₁) v₂) (ren (drop-drop v₁) t₂) sp))
| ren-∘ (exc v₁) (drop-sub-⊆ (v₁ - v₂) ∘ sub-drop- v₁)(sub v₂ t₂ t₁)
| remove- v₁ v₂
| sym $ sub-sub-Sp v₁ v₂ t₁ t₂ sp
| sub-◇
(ren-∈ (drop-sub-⊆ v₁) v₂)
(ren (⊆-drop v₂ (drop-sub-⊆ v₁)) t₂)
(ren (drop-sub-⊆ v₁) t₁)
(subSp v₁ t₁ sp)
| sym $ ren-sub v₂ (drop-sub-⊆ v₁) t₂ t₁
= refl
-- Substitute t₂
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ _)
with ∈-eq v₁ v
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ (_ , _ , () , _ , _)) | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ (_ , v' , refl , _ , _)) | inj₂ _
with ∈-eq (ren-∈ (drop-sub-⊆ v₁) v₂) v'
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ (_ , _ , refl , _ , ())) | inj₂ _ | inj₂ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ (_ , _ , refl , _ , _ )) | inj₂ _ | inj₁ refl
with ∈-eq (ren-∈ (drop-⊆ v₁) v₂) v
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ (_ , _ , refl , () , _)) | inj₂ _ | inj₁ refl | inj₂ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₁ (_ , v' , refl , _ , _)) | inj₂ _ | inj₁ refl | inj₁ refl
rewrite
ren-∘ (drop-sub-⊆ (ren-∈ (drop-sub-⊆ v₁) v₂))
(drop-drop-sub v₁) t₂
| ren-∘ (drop-sub-⊆ (ren-∈ (drop-⊆ v₁) v₂))
(⊆-drop v₂ (drop-⊆ v₁)) t₂
| sub-◇
(v₁ - v₂)
(ren (sub-drop- v₁) (sub v₂ t₂ t₁))
(ren (drop-sub-⊆ (ren-∈ (drop-⊆ v₁) v₂) ∘ ⊆-drop v₂ (drop-⊆ v₁)) t₂)
(subSp (ren-∈ (drop-⊆ v₁) v₂) (ren (⊆-drop v₂ (drop-⊆ v₁)) t₂) sp)
| ren-◇
(exc v₁)
(sub (v₁ - v₂)
(ren (sub-drop- v₁) (sub v₂ t₂ t₁))
(ren (drop-sub-⊆ (ren-∈ (drop-⊆ v₁) v₂) ∘ ⊆-drop v₂ (drop-⊆ v₁)) t₂))
(subSp (v₁ - v₂) (ren (sub-drop- v₁) (sub v₂ t₂ t₁))
(subSp (ren-∈ (drop-⊆ v₁) v₂) (ren (⊆-drop v₂ (drop-⊆ v₁)) t₂) sp))
| sym $ sub-sub-Sp v₁ v₂ t₁ t₂ sp
| fresh-sub
(drop-sub-⊆ (ren-∈ (drop-⊆ v₁) v₂) ∘ ⊆-drop v₂ (drop-⊆ v₁))
(v₁ - v₂)
(Fresh- v₁ v₂)
(ren (sub-drop- v₁) (sub v₂ t₂ t₁))
t₂
| ren-∘
(exc v₁)
(Fresh-sub-⊆
(drop-sub-⊆ (ren-∈ (drop-⊆ v₁) v₂) ∘ ⊆-drop v₂ (drop-⊆ v₁))
(Fresh- v₁ v₂))
t₂
| remove-Fresh- v₁ v₂
= refl
-- Substitute nothing
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ _)
with ∈-eq v₁ v
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (_ , _ , _ , _ , () , _ , _ , _ , _)) | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (v' , _ , _ , _ , refl , _ , _ , _ , _)) | inj₂ _
with ∈-eq (ren-∈ (drop-sub-⊆ v₁) v₂) v'
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (_ , _ , _ , _ , refl , _ , _ , () , _)) | inj₂ _ | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (_ , _ , _ , _ , refl , _ , _ , _ , _)) | inj₂ _ | inj₂ _
with ∈-eq (ren-∈ (drop-⊆ v₁) v₂) v
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (_ , _ , _ , _ , refl , _ , () , _ , _)) | inj₂ _ | inj₂ _ | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (v' , v'' , _ , _ , refl , _ , refl , _ , _)) | inj₂ _ | inj₂ _ | inj₂ _
with ∈-eq (v₁ - v₂) v''
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (_ , _ , _ , _ , refl , () , refl , _ , _ )) | inj₂ _ | inj₂ _ | inj₂ _ | inj₁ _
sub-sub v₁ v₂ t₁ t₂ (ne (v , sp)) | inj₂ (inj₂ (_ , _ , _ , _ , refl , refl , refl , refl , refl)) | inj₂ _ | inj₂ _ | inj₂ _ | inj₂ _
= cong (λ x → ne (_ , x)) (sub-sub-Sp v₁ v₂ t₁ t₂ sp)
sub-sub-Sp :
∀ {Γ A B C D}
(v₁ : A ∈ Γ)(v₂ : B ∈ drop v₁)
(t₁ : Ty (drop v₁) A)(t₂ : Ty (drop v₂) B)
(sp : Sp Γ C D)
→ subSp (ren-∈ (drop-sub-⊆ v₁) v₂) (ren (drop-drop-sub v₁) t₂) (subSp v₁ t₁ sp)
≡ renSp (exc v₁) (subSp (v₁ - v₂) (ren (sub-drop- v₁) (sub v₂ t₂ t₁))
(subSp (ren-∈ (drop-⊆ v₁) v₂) (ren (drop-drop v₁) t₂) sp))
sub-sub-Sp v₁ v₂ t₁ t₂ ε = refl
sub-sub-Sp v₁ v₂ t₁ t₂ (t ∷ sp) =
cong₂ _∷_ (sub-sub v₁ v₂ t₁ t₂ t) (sub-sub-Sp v₁ v₂ t₁ t₂ sp)
sub-inst :
∀ {Γ A B C}(v : A ∈ Γ) t₁ t₂ (t : Ty (Γ ▷ B) C) →
sub v t₂ (inst t₁ t) ≡ inst (sub v t₂ t₁) (sub (vs v) t₂ t)
sub-inst v t₁ t₂ t rewrite
sym $ ren-refl t₂ -- would be nice to rewrite "ren refl" to "id"
| sub-sub vz v t₁ t₂ t | ren-refl (sub v t₂ t₁) | ren-refl t₂
| ren-refl (sub vz (sub v t₂ t₁) (sub (vs v) t₂ t))
= refl
sub-◇ :
∀ {Γ A B C}(v : A ∈ Γ) t' (t : Ty Γ B)(sp : Sp Γ B C)
→ sub v t' (t ◇ sp) ≡ (sub v t' t ◇ subSp v t' sp)
sub-◇ v t' t ε = refl
sub-◇ v t' (ƛ t) (x ∷ sp) rewrite
sub-◇ v t' (inst x t) sp | sub-inst v x t' t = refl
-- Correctness of eta-expansion
--------------------------------------------------------------------------------
ηᶜ : ∀ {Γ A} → A ∈ Γ → Con
ηᶜ {Γ ▷ A} vz = Γ ▷ A ▷ A
ηᶜ {Γ ▷ B} (vs v) = ηᶜ v ▷ B
⊆-η : ∀ {Γ A}(v : A ∈ Γ) → Γ ⊆ ηᶜ v
⊆-η vz = keep (add refl)
⊆-η (vs v) = keep (⊆-η v)
η-∈ : ∀ {Γ A}(v : A ∈ Γ) → A ∈ drop (ren-∈ (⊆-η v) v)
η-∈ vz = vz
η-∈ (vs v) = η-∈ v
un-η : ∀ {Γ A}(v : A ∈ Γ) → Γ ⊆ subᶜ (ren-∈ (⊆-η v) v)
un-η vz = refl
un-η (vs v) = keep (un-η v)
∈-neq : ∀ {Γ A B}(v : A ∈ Γ) (v' : B ∈ subᶜ v) → ∈-eq v (ren-∈ (subᶜ-⊆ v) v') ≡ inj₂ v'
∈-neq vz v' = refl
∈-neq (vs v) vz = refl
∈-neq (vs v) (vs v') = vs-∈-≡ (∈-neq v v')
∈-eq-refl : ∀ {Γ A}(v : A ∈ Γ) → ∈-eq v v ≡ inj₁ refl
∈-eq-refl vz = refl
∈-eq-refl (vs v) = vs-∈-≡ (∈-eq-refl v)
++-ε : ∀ {Γ A B} (sp : Sp Γ A B) → sp ++ ε ≡ sp
++-ε ε = refl
++-ε (x ∷ sp) = cong (x ∷_) (++-ε sp)
++-assoc :
∀ {Γ A B C D}(sp : Sp Γ A B)(sp' : Sp Γ B C)(sp'' : Sp Γ C D)
→ (sp ++ sp') ++ sp'' ≡ sp ++ sp' ++ sp''
++-assoc ε sp' sp'' = refl
++-assoc (x ∷ sp) sp' sp'' = cong (x ∷_) (++-assoc sp sp' sp'')
renSp-++ :
∀ {Γ Δ A B C}(o : Γ ⊆ Δ)(sp : Sp Γ A B)(sp' : Sp Γ B C)
→ renSp o (sp ++ sp') ≡ renSp o sp ++ renSp o sp'
renSp-++ o ε sp' = refl
renSp-++ o (x ∷ sp) sp' = cong (ren o x ∷_) (renSp-++ o sp sp')
subSp-++ :
∀ {Γ A B C D}(v : A ∈ Γ) t' (sp : Sp Γ B C) (sp' : Sp Γ C D)
→ subSp v t' (sp ++ sp') ≡ subSp v t' sp ++ subSp v t' sp'
subSp-++ v t' ε sp' = refl
subSp-++ v t' (x ∷ sp) sp' = cong (sub v t' x ∷_) (subSp-++ v t' sp sp')
ren-η-Ne :
∀ {B Γ Δ A}(o : Γ ⊆ Δ)(v : A ∈ Γ)(sp : Sp Γ A B)
→ ren o (η-Ne (v , sp)) ≡ η-Ne (ren-∈ o v , renSp o sp)
ren-η-Ne {⋆} o v sp = refl
ren-η-Ne {A ⇒ B} o v sp
rewrite
(ren-η-Ne {B} (keep o) (vs v) (renSp top sp ++ η vz ∷ ε))
| top-comm-Sp {C = A} sp o
| renSp-++ (keep o) (renSp (add refl) sp) (η-Ne (vz , ε) ∷ ε)
| ren-η-Ne (keep {A} o) vz ε
= refl
sub-η-Ne-neq :
∀ {Γ A B C}(v : A ∈ Γ) (v' : B ∈ subᶜ v) t' (sp : Sp Γ B C)
→ sub v t' (η-Ne (ren-∈ (subᶜ-⊆ v) v' , sp)) ≡ η-Ne (v' , subSp v t' sp)
sub-η-Ne-neq {C = ⋆} v v' t' sp rewrite ∈-neq v v' = refl
sub-η-Ne-neq {A = A}{C = B ⇒ C} v v' t' sp
rewrite
sub-η-Ne-neq (vs v) (vs v') t' (renSp top sp ++ η vz ∷ ε)
| subSp-++ (vs v) t' (renSp (add refl) sp) (η-Ne (vz , ε) ∷ ε)
| subst
(λ x → subSp (vs v) x (renSp (add refl) sp)
≡ renSp (add refl) (subSp v t' sp))
(ren-refl t')
(sym (ren-sub-Sp v (add {B} refl) t' sp))
| sub-η-Ne-neq (vs v) (vz {B}) t' ε
= refl
◇-++ :
∀ {Γ A B C} (t : Ty Γ A)(sp : Sp Γ A B)(sp' : Sp Γ B C)
→ (t ◇ sp) ◇ sp' ≡ t ◇ (sp ++ sp')
◇-++ t ε sp' = refl
◇-++ (ƛ t) (x ∷ sp) sp' = ◇-++ (sub vz x t) sp sp'
η-∈-lem1 :
∀ {Γ A}(v v' : A ∈ Γ)
→ ∈-eq (ren-∈ (⊆-η v) v) (ren-∈ (⊆-η v) v') ≡ inj₁ refl
→ ren-∈ (drop-sub-⊆ (ren-∈ (⊆-η v) v)) (η-∈ v) ≡ ren-∈ (un-η v) v'
η-∈-lem1 vz vz p = refl
η-∈-lem1 vz (vs v') ()
η-∈-lem1 (vs v) vz ()
η-∈-lem1 (vs v) (vs v') p with
∈-eq (ren-∈ (⊆-η v) v) (ren-∈ (⊆-η v) v')
| inspect (∈-eq (ren-∈ (⊆-η v) v)) (ren-∈ (⊆-η v) v')
η-∈-lem1 (vs v) (vs v') p | inj₁ refl | [ eq ] = cong vs_ (η-∈-lem1 v v' eq)
η-∈-lem1 (vs v) (vs v') () | inj₂ y | [ eq ]
η-∈-lem2 :
∀ {Γ A B}(v : A ∈ Γ)(v' : B ∈ Γ)(v'' : B ∈ subᶜ (ren-∈ (⊆-η v) v))
→ ∈-eq (ren-∈ (⊆-η v) v) (ren-∈ (⊆-η v) v') ≡ inj₂ v''
→ v'' ≡ ren-∈ (un-η v) v'
η-∈-lem2 vz vz v'' ()
η-∈-lem2 vz (vs v') .(vs v') refl = refl
η-∈-lem2 (vs v) vz .vz refl = refl
η-∈-lem2 (vs v) (vs v') v'' p
with
∈-eq (ren-∈ (⊆-η v) v) (ren-∈ (⊆-η v) v')
| inspect (∈-eq (ren-∈ (⊆-η v) v)) (ren-∈ (⊆-η v) v')
η-∈-lem2 (vs v) (vs v') v'' () | inj₁ x | [ eq ]
η-∈-lem2 (vs v) (vs v') .(vs y) refl | inj₂ y | [ eq ] = cong vs_ (η-∈-lem2 v v' y eq)
mutual
η-≡ :
∀ {Γ A B}(v : A ∈ Γ)(t : Ty Γ B)
→ sub (ren-∈ (⊆-η v) v) (η (η-∈ v)) (ren (⊆-η v) t) ≡ ren (un-η v) t
η-≡ v (A ⇒ B) = cong₂ _⇒_ (η-≡ v A) (η-≡ v B)
η-≡ v (ƛ t) = cong ƛ_ (η-≡ (vs v) t)
η-≡ v (∀' k t) = cong (∀' k) (η-≡ (vs v) t)
η-≡ v (ne (v' , sp))
with
∈-eq (ren-∈ (⊆-η v) v) (ren-∈ (⊆-η v) v')
| inspect (∈-eq (ren-∈ (⊆-η v) v)) (ren-∈ (⊆-η v) v')
... | inj₁ refl | [ eq ]
rewrite
η-≡-Sp v sp
| ren-η-Ne (drop-sub-⊆ (ren-∈ (⊆-η v) v)) (η-∈ v) ε
| η-≡-◇ (ren-∈ (drop-sub-⊆ (ren-∈ (⊆-η v) v)) (η-∈ v))
ε (renSp (un-η v) sp)
| η-∈-lem1 v v' eq
= refl
... | inj₂ v'' | [ eq ]
rewrite
η-≡-Sp v sp
| η-∈-lem2 v v' v'' eq
= refl
η-≡-ƛ : ∀ {Γ A B}(f : Ty Γ (A ⇒ B)) → f ≡ (ƛ (ren top f ◇ (η vz ∷ ε)))
η-≡-ƛ (ƛ f) = cong ƛ_ (trans (sym (ren-refl f)) (sym (η-≡ vz f)))
η-≡-Sp :
∀ {Γ A B C}(v : A ∈ Γ)(sp : Sp Γ B C)
→ subSp (ren-∈ (⊆-η v) v) (η (η-∈ v)) (renSp (⊆-η v) sp) ≡ renSp (un-η v) sp
η-≡-Sp v ε = refl
η-≡-Sp v (t ∷ sp) = cong₂ _∷_ (η-≡ v t) (η-≡-Sp v sp)
η-≡-◇ :
∀ {Γ A B}(v : A ∈ Γ)(sp : Sp Γ A B)(sp' : Sp Γ B ⋆)
→ η-Ne (v , sp) ◇ sp' ≡ ne (v , (sp ++ sp'))
η-≡-◇ v sp ε = cong (λ x → ne (v , x)) (sym (++-ε sp))
η-≡-◇ v sp (x ∷ sp')
rewrite
sub-η-Ne-neq vz v x (renSp top sp ++ η vz ∷ ε)
| subSp-++ vz x (renSp (add refl) sp) (η-Ne (vz , ε) ∷ ε)
| inst-top-Sp x sp
| sub-η-Ne-eq vz x ε
| ren-refl x
| η-≡-◇ v (sp ++ x ∷ ε) sp'
| ++-assoc sp (x ∷ ε) sp'
= refl
sub-η-Ne-eq :
∀ {B Γ A}(v : A ∈ Γ) t' (sp : Sp Γ A B)
→ sub v t' (η-Ne (v , sp)) ≡ (ren (drop-sub-⊆ v) t' ◇ subSp v t' sp)
sub-η-Ne-eq {⋆} v t' sp rewrite ∈-eq-refl v = refl
sub-η-Ne-eq {A ⇒ B} v t' sp
rewrite
sub-η-Ne-eq {B} (vs v) t' (renSp top sp ++ η vz ∷ ε)
| subSp-++ (vs v) t' (renSp (add refl) sp) (η-Ne (vz , ε) ∷ ε)
| subst (λ x → subSp (vs v) x (renSp (add refl) sp)
≡ renSp (add refl) (subSp v t' sp))
(ren-refl t')
(sym (ren-sub-Sp v (add {A} refl) t' sp))
| sub-η-Ne-neq (vs v) (vz {A}) t' ε
| η-≡-ƛ (ren (drop-sub-⊆ v) t' ◇ subSp v t' sp)
| ren-◇ (top {A}) (ren (drop-sub-⊆ v) t') (subSp v t' sp)
| ren-∘ (top {A}) (drop-sub-⊆ v) t'
| ◇-++ (ren (add (drop-sub-⊆ v)) t')
(renSp (add refl) (subSp v t' sp))
(η-Ne (vz , ε) ∷ ε)
= refl
η-inst : ∀ {Γ A B} (t : Ty (Γ ▷ A) B) → inst (η vz) (ren (keep top) t) ≡ t
η-inst t = trans (η-≡ vz t) (ren-refl t)